Odpowiedzi

  • Użytkownik Zadane
2013-07-15T19:54:50+02:00

(x-3)(2x+2)=(x-3)(x²-6)

(x-3)(2x+2) - (x-3)(x²-6) = 0

(x - 3) [ (2x + 2) - (x² - 6) ] = 0

x - 3 = 0    lub  2x +2 - x² + 6 = 0

x = 3                 -x² + 2x + 8 = 0

                         x² - 2x - 8 = 0

                         Δ = 4 - 4 * 1 * (-8) = 4 + 32 = 36

                         √Δ = 6

                         x1 = (2 - 6)/2 = -4/2 = -2

                         x2 = (2 + 6)/2 = 8/2 = 4

 

odp. x = 3  lyb  x = -2   lub  x = 4

1 5 1